Early Versus Late Amniotomy in Nulliparous Women Undergoing Induction of Labor [20E]. (May 2018) - Doulaveris, Georgios; Powell, Kristin; Fisher, Nelli; Frieden, Faith; Stone, Joanne; Bernstein, Peter
Abstract : INTRODUCTION: Our objective was to investigate the effect of early versus late amniotomy on obstetric and neonatal outcomes in nulliparous women undergoing induction of labor. METHODS: This was a retrospective cohort analysis of nulliparous patients undergoing induction of labor in seven academic New York hospitals over one year (2016) derived from a quality improvement database. Nulliparous women with a singleton gestation undergoing induction of labor requiring an amniotomy were included. Data selected for this analysis included timing of amniotomy, obstetric and neonatal outcomes. Early amniotomy was defined as artificially ruptured membranes prior to the active phase and late amniotomy after the onset of active phase of labor. Results were compared between early and late amniotomy groups. Standard univariate analyses were performed. RESULTS: 7104 medical charts were reviewed. 411 (5.8%) patients were nulliparous, undergoing induction of labor that required artificial rupture of membranes. 249 (60.6%) patients had an early and 162 (39.4%) patients had a late amniotomy. There was no statistically significant difference in the two groups in the rates of cesarean delivery (17.8% vs. 16%), operative delivery (10.8% vs. 8%), chorioamnionitis (5% vs. 6.8%), admission to neonatal ICU (6.6% vs. 8.6%) or an Apgar score less than 7 at one minute (7% vs. 6.2%). Women that underwent an early amniotomy had shorter active phase of labor (277.1 ± 11.4 mins vs. 347.8 ± 19.8 mins, p= 0.0009). CONCLUSION: Early amniotomy in nulliparous women undergoing induction of labor may shorten the active phase of labor without increasing the risk of adverse obstetric or neonatal outcomes.